2017
DOI: 10.3390/cosmetics4040054
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Potential of a Liotropic Liquid Crystal Emulsion Containing Resveratrol

Abstract: Abstract:Resveratrol is a natural substance that has been the target of many researchers over the years since it presents a variety of potential applications in the areas of cosmetics and medicine as a treatment for some diseases. Due to its high antioxidant capacity but low bioavailability, we evaluated the antiaging potential of resveratrol as a liotropic liquid crystal emulsion. Initially, we performed in vitro assays to quantify both the organoleptic characteristics and stability of the emulsion. Next, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This is because the surfactants that used in the EVOO liquid crystal emulsion (alkyl polyglycosides and caprylic triglycerides) are forming a lamellar liquid crystal structure. The structure of the lamellar liquid crystal is very dependent on the structure of the alkyl polyglycoside [4,15]. The liquid crystal phase has some characteristics like solid and more organized like liquid, characterized by the ability to flow [16], it made the emulsions to be stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the surfactants that used in the EVOO liquid crystal emulsion (alkyl polyglycosides and caprylic triglycerides) are forming a lamellar liquid crystal structure. The structure of the lamellar liquid crystal is very dependent on the structure of the alkyl polyglycoside [4,15]. The liquid crystal phase has some characteristics like solid and more organized like liquid, characterized by the ability to flow [16], it made the emulsions to be stable.…”
Section: Discussionmentioning
confidence: 99%
“…Skin aging occurs just like the aging of body cells in general, which is the accumulation of endogenous damage due to the formation of Reactive Oxygen Species (ROS) during cellular oxidation metabolism [3]. ROS causes oxidative stress on biological structures, which ultimately has an impact on physical appearance and biochemical changes causing phenotypic consequences such as expression lines, low hydration, and pigmentation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The compound, however, does not affect 5α-dihy-drotestosterone, 5α-reductase or oestrogen-related gamma receptor without participating in the production of collagen associated with the change in the concentration of these compounds (this happens due to the action on the oestrogen-related α receptor and oestrogen-related β receptor) [ 11 , 12 ]. Polyphenol inhibits tyrosinase, reducing skin discoloration and smoothes wrinkles through activity against granulocyte-macrophage colony-stimulating factor (GM-CSF) and matrix metalloproteinase 1 (MMP-1) [ 13 16 ].…”
Section: Slowing Down the Aging Process Of The Skinmentioning
confidence: 99%
“…In some of the patients, pigmentation increased (4 people – the forehead, 5 people – the buccal area). It was found that the cream had no significant effect on wrinkle reduction and water retention, preventing dry skin [ 11 ].…”
Section: Slowing Down the Aging Process Of The Skinmentioning
confidence: 99%